2021
DOI: 10.1111/1475-6773.13645
|View full text |Cite
|
Sign up to set email alerts
|

Did Medicaid slow declines in access to health care during the great recession?

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Our findings, only lightly explored in the literature at present, suggest Medicaid could be playing even larger roles as protecting people from the financial effects of employment shocks and transient poverty. As Medicaid seemingly played a familiar role for individuals and families falling victim to recession-linked job losses in the Great Recession of 2007−2009,47,48 our findings suggest expanded access to Medicaid may buffer the disruptions in health care access stemming from job instability during the COVID-19 pandemic and near future periods of economic uncertainty.…”
Section: Discussionmentioning
confidence: 78%
“…Our findings, only lightly explored in the literature at present, suggest Medicaid could be playing even larger roles as protecting people from the financial effects of employment shocks and transient poverty. As Medicaid seemingly played a familiar role for individuals and families falling victim to recession-linked job losses in the Great Recession of 2007−2009,47,48 our findings suggest expanded access to Medicaid may buffer the disruptions in health care access stemming from job instability during the COVID-19 pandemic and near future periods of economic uncertainty.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the results support those of previous studies describing the use of broader eligibility guidelines for Medicaid to facilitate unemployment-related Medicaid enrollment during economic downturns (eg, the Great Recession from 2007 to 2009) and the increased accessibility to Medicaid among those affected by local economic downturns after passage of the ACA. In combination with other recent studies, we believe that this study’s findings provide support for potentially stabilizing access to care through Medicaid expansion for households affected by job loss.…”
Section: Discussionmentioning
confidence: 99%
“…We find that a one percentage point (PPT) increase in the local unemployment rate is associated with a 1.7 PPT (7.8%, p < 0.01) increase in the uninsurance rate among states with restrictive eligibility guidelines and low reimbursement fees (i.e., our reference group). Using a similar approach, Benitez et al (2021) found rising county-level unemployment to be associated with a 1.3 PPT (95% CI: 0.9, 1.6) increase in the likelihood of being uninsured among states with the most restrictive Medicaid eligibility guidelines during the Great Recession period (Benitez, Perez, et al, 2021). We found the relationship between unemployment and uninsurance was statistically similar in states with restrictive eligibility guidelines and high provider fees (−0.27 PPT, p > 0.10).…”
Section: Health Insurance Coverage and Care Accessmentioning
confidence: 99%
“…Unemployment-linked Medicaid enrollments-transitions to Medicaid coverage after a job loss among people previously insured by private (e.g., employer-based) health insurance plans-could signal households leveraging the Medicaid program to maintain access to health care and even buffer the adverse health and non-health effects normally associated with job loss such as 1426 -Health Economics. 2024;33:1426-1453. wileyonlinelibrary.com/journal/hec © 2024 John Wiley & Sons Ltd. inability to afford needed care or obtain prescription drugs because of cost constraint (Benitez et al, 2023;Benitez, Perez, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%